Privacidade em redes sociais: uma análise da experiência dos usuários - Simone Isabela de Rezende Xavier (2014)
Since 1997, when the first online social network (OSN) was launched, many others have emerged and their use have been growing and becoming more popular around the world. However, despite its benefits, with their popularity also arises privacy concerns in these environments. Thereafter several studies have shown the importance of investigating privacy in social networks and have tried to understand the users behavior. This work aims at bringing contributions to the understanding of how these users perceive and deal with privacy in social networks with focus on the contrast between their experience in social networks in the physical and virtual world. Furthermore, the results show there are several points at which social networks are not meeting the needs of users of online social networks and which strategies they are adopting to circumvent these situations. To do that, qualitative analysis were performed through interviews and quantitative analysis were performed through an online survey. Based on the main issues identified from users experience an inspection of a social network was carried out and interaction decisions that contributed to the problems were discussed.